The Claustrum: charting a way forward for the brain's most mysterious nucleus - Ariel Y Deutch (Frontiers Research Topics, 2015)
The claustrum is a long, band-like grey matter structure situated in the ventrolateral telencephalon of most, if not all, mammalian brains. Due to its shape and close proximity to white matter structures and insular cortex, the anatomy and behavioral relevance of the claustrum have proven difficult to study. As a result, disagreements in the literature exist over ontogeny, phylogeny, anatomical boundaries, and connectivity. Despite this, it is generally regarded that the claustrum contains excitatory projection neurons that reciprocally connect to most regions of the cerebral cortex, a feature that has fostered varying hypotheses as to its function. These hypotheses propose multisensory integration, coordination of cortical activity for the generation of conscious percepts, or saliency filtration. The articles of this e-book consider the historical and recent highlights in claustrum structure, hodology, and function and seek to provide a compelling way forward for this "hidden" nucleus.